Could an event of extreme drought (2019-2020) affect the feeding ecology of Bubo magellanicus (Gmelin 1788) (Strigiformes: Strigidae) in a Mediterranean region of Chile? - Sam Catchpole Ahumada; Luis Carrera Suárez; Reinaldo Rivera (PeerJ, 2023)
Global warming generates changes in environmental conditions, affecting the spatial-temporal dynamics of precipitation and temperature. Droughts, events of low rainfall, are becoming more frequent and severe. In central Chile, from 2010 to date, an unprecedented drought event has developed, affecting the ecosystem and creating pressure on the dynamics of food webs. The present study analysed the trophic ecology of Bubo magellanicus, a top predator in the Mediterranean region of Chile, between 2019 and 2020 a period with a rainfall deficit of 72.6%. Our results established a diet mainly described by invertebrates (97.75%), in particular by the Gramnostola rosea spider (87.86%), and a low contribution of small vertebrates (2.24%). The trophic niche breadth (B = 0.37) and the standardised Levin’s index (BSTA = 0.01) are the lowest recorded in the species B. magellanicus. A comparative analysis of trophic ecology with other studies developed in the same region established significant differences in the composition of the diet (frequency of occurrence of prey unit). This work provides evidence that droughts and other extreme environmental scenarios restructure the food webs of an ecosystem, with direct consequences on the trophic niche of the species, specifically top predators.